MdNAC4 Interacts With MdAPRR2 to Regulate Nitrogen Deficiency-Induced Leaf Senescence in Apple (Malus domestica) - Wen, Binbin; Gong, Xingyao; Tan, Qiuping; Zhao, Wenzhe; Chen, Xiude; Li, Dongmei; Li, Ling; Xiao, Wei (Frontiers in Plant Science, 2022)
Nitrogen (N) is one of the important macronutrients in plants, and N deficiency induces leaf senescence. However, the molecular mechanism underlying how nitrogen deficiency affects leaf senescence is unclear. Here, we report an apple NAC TF, MdNAC4, that participates in N deficiency-induced leaf senescence. The senescence phenotype of apple leaves overexpressing MdNAC4 was enhanced after N deficiency. Consistently, the chlorophyll content of transgenic leaves was significantly lower than that in the WT control leaves, the expression of chlorophyll degradation-related genes (MdNYC1, MdPAO, and MdSGR1) was significantly higher than that in the WT controls, and the expression of chlorophyll synthesis-related genes (MdHEMA, MdCHLI, and MdCHLM) was significantly lower than that in the WT control leaves. Furthermore, MdNAC4 was found to directly activate the transcription of the chlorophyll catabolism-related genes MdNYC1 and MdPAO. Additionally, MdNAC4 was proven to interact with MdAPRR2 proteins both in vitro and in vivo, and overexpression of MdAPRR2 seemed to delay N deficiency-induced leaf senescence. Correspondingly, the chlorophyll loss of MdAPRR2-overexpressing plants was significantly lower than in WT control plants. Although downregulated, the expression of the chlorophyll synthesis-related genes MdHEMA, MdCHLI, and MdCHLM in the transgenic plants was more than twice that in the WT control plants. Taken together, our results enrich the regulatory network of leaf senescence induced by N deficiency through the interaction between MdNAC4 and MdAPRR2.